Uses and Gratifications dalam Media Sosial Algoritmik: Tantangan dan Kesenjangan antara Gratifications Sought dan Gratifications Obtained - Lisnarti, Lisnarti (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
This research is a conceptual study that aims to examine the relevance of the Uses and Gratifications (U&G) theory in the context of social media use in the increasingly algorithmic digital era. Using a descriptive qualitative approach based on literature review, this article analyzes the development of U&G theory from traditional media to interactive social media, and examines the expansion of gratification categories that have emerged in contemporary digital platforms. The results of the study indicate that although U&G theory remains relevant to explaining motives for social media use, there is a significant gap between gratifications sought (GS) and gratifications obtained (GO). Users often seek social connection, self-expression, and identity validation, but in practice, they experience digital fatigue, social anxiety, and decreased psychological well-being. This gap is further exacerbated by the role of platform algorithms that limit users' conscious choices through data-driven content curation. This finding distinguishes this article from previous U&G studies that tend to emphasize user gratification without critiquing the structural dimensions of social media. Theoretically, this article contributes to the development of U&G by emphasizing the importance of integrating classic gratifications, new gratifications, and critiques of algorithmic systems to ensure the theory remains relevant in explaining contemporary social media user behavior.